Relationship in nucleic acid sequences between mouse mammary tumor virus variants. - Michalides, R (1975)
Primary cultures of mouse mammary carcinomas were used as a source of both radioactively labeled and unlabeled 60-70S RNA of mouse mammary tumor virus (MMTV) obtained from various mouse strains. Competition molecular hybridization experiments revealed that, within the limits of the assay, the RNAs of the MMTVs synthesized in culture by the tumors of the mouse strains RIII, GR, A, and C3H, are identical. A comparison of the genomes of the milk-transmitted MMTV(C3H) and the vertically transmitted MMTV(C3Hf) revealed that these two viruses are approximately 75% similar. No nucleic acid sequence homology was observed between MMTV(C3H) 60-70S RNA and the RNAs of murine leukemia virus, Mason-Pfizer virus, or the BrdUrd-induced type-B quinea pig virus.